Active energy ray-curable peelable adhesive composition and adhesive sheet
The active energy ray curable peelable adhesive composition, featuring an acrylic resin, urethane (meth)acrylate, and a nitroso compound, addresses the challenges of maintaining adhesive strength at high temperatures and ensuring easy peelability without residue, achieving effective temporary surface protection in manufacturing processes.
Patent Information
- Application Number
- JP2024177144
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-03-26
- Filing Date
- 2024-10-09
- Publication Date
- 2025-04-24
AI Technical Summary
Existing adhesive compositions for temporary surface protection in manufacturing processes, such as those for semiconductor wafers and printed circuit boards, face challenges in maintaining adequate adhesive strength at high temperatures and ensuring easy peelability without leaving residue.
An active energy ray curable peelable adhesive composition is developed, containing an acrylic resin, urethane (meth)acrylate, and a specific nitroso compound as a polymerization inhibitor. This composition provides excellent adhesive strength before irradiation, maintains strength at high temperatures, and reduces adhesive strength after irradiation, enabling easy peelability without residue.
The adhesive composition achieves excellent adhesive strength before active energy ray irradiation, maintains strength under high temperature conditions, and ensures easy peelability with no adhesive residue after irradiation, addressing the limitations of existing technologies.
Smart Images

Figure 2025067860000001 
Figure 2025067860000002 
Figure 2025067860000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to an active energy ray-curable peel-type pressure-sensitive adhesive composition and a pressure-sensitive adhesive sheet, and more specifically to a pressure-sensitive adhesive composition used as a pressure-sensitive adhesive for a peel-type pressure-sensitive adhesive sheet for temporary surface protection when processing workpieces such as semiconductor wafers, printed circuit boards, processed glass products, metal plates, plastic plates, etc., and particularly to an active energy ray-curable peel-type pressure-sensitive adhesive composition and a pressure-sensitive adhesive sheet. [Background technology]
[0002] Conventionally, in the processing steps such as the manufacture of integrated circuits using semiconductor wafers and drilling holes, adhesive sheets for surface protection are used to temporarily protect the surface of the workpiece in order to prevent the workpiece from being soiled or damaged.In recent years, due to the miniaturization of processing technology and the thinning of workpieces, etc., a moderate adhesive strength is required for the workpiece, while after the surface protection role is completed, the adhesive sheet for surface protection needs to be peeled off, and when peeling, it is required to be peeled off with a light force without leaving any adhesive residue.In addition, in recent years, adhesive sheets for surface protection are used not only for semiconductor wafers but also for the processing of various other parts.
[0003] For such adhesive sheets, an active energy ray-curable adhesive composition that can be cured by irradiation with active energy rays and reduce adhesive strength is effective. For example, active energy ray-curable properties are exhibited by (1) blending a monomer and / or oligomer having an ethylenically unsaturated group with an acrylic resin, or (2) using an ethylenically unsaturated group-containing acrylic resin in which the acrylic resin itself contains an ethylenically unsaturated group.
[0004] In recent years, in the manufacturing process of electronic components, components with adhesive tape attached are often exposed to high temperatures. Therefore, adhesive tapes used in the manufacturing process of electronic components are required to have heat resistance so that they can withstand high temperature conditions. For example, Patent Document 1 discloses an adhesive sheet coated with an active energy ray-curable adhesive having a glass transition temperature of -50°C or higher and 10°C or lower, and describes that even after heat treatment, the adhesive strength between the wafer chip and the adhesive sheet decreases after irradiation with active energy rays, allowing the wafer chip to be easily picked up.
[0005] Furthermore, Patent Document 2 describes a pressure-sensitive adhesive that is excellent as a removable pressure-sensitive adhesive even after being exposed to high temperature and humid heat conditions, by incorporating a phosphorus-based antioxidant into an acrylic resin.
[0006] Furthermore, Patent Document 3 describes an active energy ray-curable adhesive that contains a hindered phenol-based antioxidant, and thereby has excellent removability even after being exposed to high temperature and humid heat conditions. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2020 / 100491 [Patent Document 2] Japanese Patent Application Publication No. 2020-158691 [Patent Document 3] Japanese Patent Application Publication No. 2019-145575 Summary of the Invention [Problem to be solved by the invention]
[0008] However, in the technology disclosed in Patent Document 1, although the adhesive strength is reduced by irradiation with active energy rays after heat treatment at 150°C and peelability is exhibited, there is a problem that sufficient peelability cannot be obtained under heat treatment conditions at higher temperatures, for example, 175 to 200°C, and the technology is still not satisfactory.
[0009] Furthermore, even the techniques disclosed in Patent Documents 2 and 3 have the problem that sufficient peelability cannot be obtained under higher temperature conditions, and are still unsatisfactory.
[0010] Therefore, under such circumstances, the present invention aims to provide an active energy ray-curable peel-type pressure-sensitive adhesive composition that has good adhesive strength before irradiation with active energy rays, that prevents an extreme decrease in adhesive strength even when exposed to high temperatures, and that reduces adhesive strength after irradiation with active energy rays, and that can give a pressure-sensitive adhesive with excellent peelability and no adhesive residue. [Means for solving the problem]
[0011] However, the present inventors have conducted extensive research in light of these circumstances and have found that by using a nitroso compound as a polymerization inhibitor in an adhesive composition containing an acrylic resin and a urethane (meth)acrylate as an adhesive composition, it is possible to obtain an adhesive that has good adhesive strength before irradiation with active energy rays, that is prevented from decreasing drastically even when exposed to high temperatures, and that has reduced adhesive strength after irradiation with active energy rays and excellent peelability without leaving any adhesive residue, thereby completing the present invention.
[0012] That is, the present invention has the following aspects [1] to
[14] . [1] An active energy ray-curable peel-off pressure-sensitive adhesive composition containing an acrylic resin (A), a urethane (meth)acrylate compound (B), and a polymerization inhibitor (C), The active energy ray-curable peel-type pressure-sensitive adhesive composition, wherein the polymerization inhibitor (C) contains a nitroso compound (C1). [2] The active energy ray-curable peelable pressure-sensitive adhesive composition according to [1], wherein the acrylic resin (A) has a structural unit derived from an alkyl(meth)acrylate (a1). [3] The active energy ray-curable peelable pressure-sensitive adhesive composition according to [1] or [2], wherein the acrylic resin (A) has a structural unit derived from a functional group-containing monomer (a2). [4] The active energy ray-curable peelable pressure-sensitive adhesive composition according to any one of [1] to [3], wherein the acrylic resin (A) has a structural unit derived from a hydroxyl group-containing monomer (a2-1). [5] The active energy ray-curable peel-type pressure-sensitive adhesive composition according to [4], wherein the content of the structural units derived from the hydroxyl group-containing monomer (a2-1) is 0.1 to 10 mass % of all structural units of the acrylic resin (A). [6] The active energy ray-curable peelable pressure-sensitive adhesive composition according to any one of [1] to [5], wherein the acrylic resin (A) has a structural unit derived from a carboxy group-containing monomer (a2-2). [7] The active energy ray-curable peel-type pressure-sensitive adhesive composition according to [6], wherein the content of the structural units derived from the carboxy group-containing monomer (a2-2) is 0.1 to 10 mass % of all structural units of the acrylic resin (A). [8] The active energy ray-curable peelable pressure-sensitive adhesive composition according to any one of [1] to [7], wherein the urethane (meth)acrylate compound (B) has 5 to 20 ethylenically unsaturated groups. [9] The active energy ray-curable peel-type pressure-sensitive adhesive composition according to any one of [1] to [8], wherein the urethane (meth)acrylate compound (B) is a reaction product of a hydroxyl group-containing (meth)acrylate compound containing three or more ethylenically unsaturated groups in the molecule and a polyvalent isocyanate compound (b2).
[10] The active energy ray-curable peelable pressure-sensitive adhesive composition according to any one of [1] to [9], wherein the nitroso compound (C1) is ammonium N-nitrosophenylhydroxylamine and / or N-nitrosophenylhydroxylamine aluminum salt.
[11] The active energy ray-curable peelable pressure-sensitive adhesive composition according to any one of [1] to
[10] , further comprising a crosslinking agent (D).
[12] The active energy ray-curable peelable pressure-sensitive adhesive composition according to any one of [1] to
[11] , further comprising a photopolymerization initiator (E).
[13] A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer crosslinked with the active energy ray-curable peelable pressure-sensitive adhesive composition according to any one of [1] to
[12] .
[14] The pressure-sensitive adhesive sheet according to
[13] , wherein the pressure-sensitive adhesive layer is cured and becomes peelable upon irradiation with active energy rays. [Effects of the Invention]
[0013] The active energy ray-curable peel-type pressure-sensitive adhesive composition of the present invention contains an acrylic resin, a urethane (meth)acrylate, and a specific polymerization inhibitor, and therefore has good adhesive strength before exposure to active energy rays, and is prevented from excessively decreasing in adhesive strength even when exposed to high temperatures. Furthermore, after exposure to active energy rays, the adhesive strength is reduced even when exposed to high temperatures, and the pressure-sensitive adhesive has excellent peelability without leaving any adhesive residue. DETAILED DESCRIPTION OF THE INVENTION
[0014] Hereinafter, embodiments for carrying out the present invention will be specifically described, but the present invention is not limited to these. In this specification, "(meth)acrylic" means acrylic or methacrylic, "(meth)acryloyl" means acryloyl or methacryloyl, and "(meth)acrylate" means acrylate or methacrylate, respectively. In this specification, the term "sheet" is not particularly distinguished from "film" or "tape" and is used to include these terms.
[0015] In this specification, when the expression "X to Y" (X and Y are any numbers) is used, unless otherwise specified, it means "X or more and Y or less," as well as "preferably more than X" or "preferably less than Y." In this specification, "x and / or y (x and y are optional configurations)" means at least one of x and y, and can mean three possibilities: x only, y only, or x and y. In the present specification, when numerical ranges are described in stages, the upper or lower limit of a certain numerical range can be arbitrarily combined with the upper or lower limit of another numerical range. In addition, in the numerical ranges described in this specification, the upper or lower limit of the numerical range can also be replaced with the values shown in the examples.
[0016] In the detailed description of the present invention, the copolymerization ratio of (meth)acrylate monomers constituting the acrylic resin and the blending amounts of other compounds may be expressed as "% by mass" or "parts by mass," which means on a mass basis. For example, the mass% of an acrylic resin is the ratio when all copolymerization components are taken as 100%.
[0017] An active energy ray-curable peelable pressure-sensitive adhesive composition according to one embodiment of the present invention (hereinafter sometimes referred to as "the present pressure-sensitive adhesive composition") is mainly used in the pressure-sensitive adhesive layer of a pressure-sensitive adhesive sheet, which is generally intended to be peeled off after being attached to a workpiece such as a metal plate, a plastic plate, a semiconductor wafer, etc. The pressure-sensitive adhesive sheet is formed by coating the present pressure-sensitive adhesive composition on a substrate sheet to form a pressure-sensitive adhesive layer, and after being attached to the workpiece, the pressure-sensitive adhesive layer is cured by irradiating it with active energy rays, reducing the adhesive strength, and allowing it to be easily peeled off from the workpiece.
[0018] The present pressure-sensitive adhesive composition contains an acrylic resin (A), a urethane (meth)acrylate compound (B), and a polymerization inhibitor (C). Each of the components of the present pressure-sensitive adhesive composition will be described below.
[0019] [Acrylic resin (A)] The acrylic resin (A) is a resin obtained by polymerizing a polymerization component containing at least one kind of (meth)acrylate monomer.
[0020] The acrylic resin (A) preferably has a structural unit derived from an alkyl (meth)acrylate (a1), a structural unit derived from a functional group-containing monomer (a2), and, if necessary, a structural unit derived from another copolymerizable monomer (a3). Such an acrylic resin (A) is preferably obtained by copolymerizing copolymerization components containing an alkyl (meth)acrylate (a1), a functional group-containing monomer (a2), and, if necessary, other copolymerizable monomers (a3), etc. The content of each monomer relative to the total copolymerization components can be considered to be the content of structural units derived from that monomer in the acrylic resin (A) which is a copolymer. For example, the content of the acrylic (meth)acrylate (a1) relative to the total copolymerization components is considered to be the content of structural units derived from the acrylic (meth)acrylate (a1) in the acrylic resin (A).
[0021] [Alkyl (meth)acrylate (a1)] The alkyl group of the alkyl (meth)acrylate (a1) preferably has 1 to 20 carbon atoms, particularly preferably 1 to 12, and even more preferably 1 to 8. When the number of carbon atoms is within the above range, adhesive residue on the workpiece tends to be less likely to occur.
[0022] Examples of the alkyl (meth)acrylate (a1) include aliphatic alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-propyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, and isostearyl (meth)acrylate; and alicyclic alkyl (meth)acrylates such as cyclohexyl (meth)acrylate and isobornyl (meth)acrylate. These may be used alone or in combination of two or more. Among the alkyl group-containing (meth)acrylates (a1), aliphatic alkyl (meth)acrylates are preferred, and methyl (meth)acrylate, n-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are more preferred, in terms of copolymerizability, adhesive properties, ease of handling, and ease of raw material availability.
[0023] The content of the structural units derived from alkyl (meth)acrylate (a1) in the acrylic resin (A) is usually 30 to 99.9 mass %, preferably 40 to 99 mass %, and particularly preferably 50 to 97 mass %, of the total structural units of the acrylic resin (A). When the content is within the above range, the adhesive strength before irradiation with active energy rays tends to be further improved.
[0024] [Functional group-containing monomer (a2)] The functional group-containing monomer (a2) is one other than alkyl (meth)acrylate (a1), and examples thereof include hydroxyl group-containing monomer (a2-1), carboxyl group-containing monomer (a2-2), amino group-containing monomer (a2-3), amide group-containing monomer, glycidyl group-containing monomer, sulfonic acid group-containing monomer, and acetoacetyl group-containing monomer. These functional group-containing monomers can be used alone or in combination of two or more. Among them, hydroxyl group-containing monomer (a2-1), carboxyl group-containing monomer (a2-2), and amino group-containing monomer (a2-3) are preferred.
[0025] The content of structural units derived from functional group-containing monomer (a2) in the acrylic resin (A) is usually 50% by mass or less, preferably 40% by mass or less, and more preferably 30% by mass or less, of all structural units in the acrylic resin (A). When the content is within the above range, storage stability is improved and crosslinking before the drying step can be suppressed, tending to result in excellent coatability. On the other hand, when the content is outside the above range, storage stability is reduced and crosslinking proceeds before the drying step, tending to cause problems with coatability.
[0026] The acrylic resin (A) preferably contains a structural unit derived from a hydroxyl group-containing monomer (a2-1). By using the hydroxyl group-containing monomer (a2-1) as a copolymerization component of the acrylic resin (A), the adhesion to the adherend is increased, the adhesive strength is improved, and the hydroxyl group-containing monomer (a2-1) can serve as a reaction site with the crosslinking agent (D) described below to form a crosslinked structure.
[0027] The hydroxyl group-containing monomer (a2-1) is preferably a hydroxyl group-containing (meth)acrylate monomer, and specific examples thereof include (meth)acrylic acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate, and caprolactone-modified monomers such as caprolactone-modified 2-hydroxyethyl (meth)acrylate. Examples of suitable monomers include oxyalkylene-modified monomers such as diethylene glycol (meth)acrylate and polyethylene glycol (meth)acrylate, primary hydroxyl group-containing monomers such as 2-acryloyloxyethyl-2-hydroxyethyl phthalate, secondary hydroxyl group-containing monomers such as 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate and 3-chloro-2-hydroxypropyl (meth)acrylate, and tertiary hydroxyl group-containing monomers such as 2,2-dimethyl-2-hydroxyethyl (meth)acrylate. Among the hydroxyl group-containing monomers (a2-1), primary hydroxyl group-containing monomers are preferred because of their excellent reactivity with the crosslinking agent (D) described below, and 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are particularly preferred.
[0028] When the acrylic resin (A) has a structural unit derived from a hydroxyl group-containing monomer (a2-1), the content thereof is preferably 0.1 to 10 mass % of the total structural units of the acrylic resin (A), more preferably 0.2 to 8 mass %, even more preferably 0.4 to 6 mass %, and particularly preferably 0.6 to 5 mass %. When the content is within the above range, good coatability and adhesive strength tend to be easily obtained.
[0029] The acrylic resin (A) preferably contains structural units derived from a carboxyl group-containing monomer (a2-2) and / or an amino group-containing monomer (a2-3). The carboxyl group-containing monomer (a2-2) and / or the amino group-containing monomer (a2-3) are used as copolymerization components of the acrylic resin (A), which serve as reaction sites with the crosslinking agent (D) described below to form crosslinked structures, tending to improve adhesion to the adherend and enhance adhesive strength.
[0030] Examples of the carboxy group-containing monomer (a2-2) include (meth)acrylic acid, (meth)acrylic acid dimer, crotonic acid, maleic acid, maleic anhydride, fumaric acid, citraconic acid, glutaconic acid, itaconic acid, acrylamido-N-glycolic acid, cinnamic acid, etc. Among these, (meth)acrylic acid is preferably used in terms of copolymerizability.
[0031] When the acrylic resin (A) has a structural unit derived from a carboxyl group-containing monomer (a2-2), its content is preferably 30% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, of the total structural units of the acrylic resin (A). When the content is within the above range, good coating properties and adhesive strength tend to be easily obtained. The lower limit is usually 0.01% by mass.
[0032] Examples of the amino group-containing monomer (a2-3) include aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, etc. Among these, N,N-dimethylaminoethyl (meth)acrylate is preferred.
[0033] When the acrylic resin (A) has a structural unit derived from an amino group-containing monomer (a2-3), the content thereof is usually 0.01 to 10 mass %, preferably 0.05 to 8 mass %, and more preferably 0.1 to 5 mass %, of the total structural units of the acrylic resin (A). When the content is within the above range, good coatability and adhesive strength tend to be easily obtained.
[0034] Examples of the amide group-containing monomer include (meth)acrylamide-based monomers such as methoxydimethylpropanamide, ethoxymethyl(meth)acrylamide, n-butoxymethyl(meth)acrylamide, (meth)acryloylmorpholine, dimethyl(meth)acrylamide, diethyl(meth)acrylamide, dimethylaminopropyl(meth)acrylamide, (meth)acrylamide, and N-methylol(meth)acrylamide. Among these, (meth)acryloylmorpholine is particularly preferred in terms of reducing adhesive strength after exposure to high temperatures and subsequent irradiation with active energy rays.
[0035] When the acrylic resin (A) has a structural unit derived from an amide group-containing monomer, the content thereof is usually 1 to 30 mass %, preferably 3 to 22 mass %, and more preferably 6 to 20 mass % of all structural units of the acrylic resin (A). If the content is too low, the adhesive strength after exposure to high temperatures and subsequent irradiation with active energy rays tends to be insufficient. Furthermore, since amide group-containing monomers often have a high glass transition temperature, if the content is too high, the glass transition temperature of the polymer increases, which tends to result in an insufficient adhesive strength after exposure to high temperatures and subsequent irradiation with active energy rays.
[0036] Examples of the glycidyl group-containing monomer include glycidyl methacrylate and allyl glycidyl methacrylate.
[0037] When the acrylic resin (A) has a structural unit derived from a glycidyl group-containing monomer, the content thereof is usually 20% by mass or less, preferably 10% by mass or less, and more preferably 5% by mass or less, of the total structural units of the acrylic resin (A). If the content is too high, crosslinking may proceed before the drying step, which may cause problems with coatability.
[0038] Examples of the sulfonic acid group-containing monomer include olefin sulfonic acids such as ethylene sulfonic acid, allyl sulfonic acid, and methallyl sulfonic acid, 2-acrylamido-2-methylolpropane sulfonic acid, and styrene sulfonic acid or salts thereof.
[0039] When the acrylic resin (A) has a structural unit derived from a sulfonic acid group-containing monomer, the content thereof is usually 10% by mass or less, preferably 5% by mass or less, and more preferably 1% by mass or less, of the total structural units of the acrylic resin (A). If the content is too high, crosslinking may proceed before the drying step, which may cause problems with coatability.
[0040] Examples of the acetoacetyl group-containing monomer include 2-(acetoacetoxy)ethyl (meth)acrylate and allyl acetoacetate.
[0041] When the acrylic resin (A) has a structural unit derived from an acetoacetyl group-containing monomer, the content thereof is usually 10% by mass or less, preferably 5% by mass or less, and more preferably 1% by mass or less, of the total structural units of the acrylic resin (A). If the content is too high, crosslinking may proceed before the drying step, which may cause problems with coatability.
[0042] [Other copolymerizable monomers (a3)] The other copolymerizable monomers (a3) are those other than the alkyl (meth)acrylates (a1) and the functional group-containing monomers (a2), and examples thereof include carboxylic acid vinyl ester monomers such as vinyl acetate, vinyl propionate, vinyl stearate, and vinyl benzoate; aromatic ring-containing monomers such as phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenyldiethylene glycol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, styrene, and α-methylstyrene; biphenyloxy structure-containing (meth)acrylic acid ester monomers such as biphenyloxyethyl (meth)acrylate; 2-methoxyethyl (meth)acrylate; Examples of the monomers include monomers containing an alkoxy group or an oxyalkylene group, such as acrylate, 2-ethoxyethyl (meth)acrylate, methoxydiethylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and polypropylene glycol mono(meth)acrylate; acrylonitrile, methacrylonitrile, vinyl chloride, vinylidene chloride, alkyl vinyl ether, vinyl toluene, vinylpyridine, vinylpyrrolidone, dialkyl itaconate esters, dialkyl fumarate esters, allyl alcohol, acrylic chloride, methyl vinyl ketone, allyl trimethylammonium chloride, and dimethyl allyl vinyl ketone. These may be used alone or in combination of two or more.
[0043] When the acrylic resin (A) has structural units derived from other copolymerizable monomers (a3), the content thereof is usually 40% by mass or less, preferably 30% by mass or less, and more preferably 25% by mass or less of the total structural units of the acrylic resin (A). If the content of other copolymerizable monomers (a3) is too large, the adhesive properties tend to be easily reduced.
[0044] The acrylic resin (A) is obtained by copolymerizing copolymerization components containing an alkyl (meth)acrylate (a1), a functional group-containing monomer (a2), and, if necessary, other copolymerizable monomers (a3). Such polymerization methods are typically carried out by conventionally known methods such as solution radical polymerization, suspension polymerization, bulk polymerization, and emulsion polymerization. Among these, solution radical polymerization is preferred because it allows the acrylic resin (A) to be produced safely and stably with any monomer composition.
[0045] In the solution radical polymerization, for example, copolymerization components such as alkyl (meth)acrylate (a1), functional group-containing monomer (a2), and if necessary, other copolymerizable monomers (a3), and a polymerization initiator are mixed or dropped into an organic solvent, and polymerization is carried out under reflux or generally at 50 to 98°C for about 0.1 to 20 hours.
[0046] Examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbons such as toluene and xylene, aliphatic hydrocarbons such as hexane, esters such as ethyl acetate and butyl acetate, aliphatic alcohols such as n-propyl alcohol and isopropyl alcohol, and ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. The amount of the organic solvent used is usually 10 to 900 parts by mass per 100 parts by mass of the copolymerization components.
[0047] As the polymerization initiator, a conventional radical polymerization initiator can be used, and specific examples thereof include azo-based polymerization initiators such as azobisisobutyronitrile and azobisdimethylvaleronitrile, and peroxide-based polymerization initiators such as benzoyl peroxide, lauroyl peroxide, di-tert-butyl peroxide and cumene hydroperoxide, etc. These may be used alone or in combination of two or more.
[0048] The acrylic resin (A) may be prepared by free radical polymerization or living radical polymerization.
[0049] Examples of the living radical polymerization method include the nitroxyl method (TEMPO), atom transfer radical polymerization (ATRP), and reversible addition-fragmentation chain transfer polymerization (RAFT). Among these, the ATRP and RAFT methods are preferred in terms of selectivity of the polymerization monomer, ease of control, and the like. In the present invention, the RAFT method, which uses a RAFT agent that does not use a transition metal, is particularly preferred.
[0050] The RAFT method involves carrying out normal free radical polymerization in the presence of a RAFT agent. For example, polymerization components, a RAFT agent, and a polymerization initiator are mixed in a reaction solvent and then polymerization is carried out.
[0051] Furthermore, the acrylic resin (A) prepared by living radical polymerization may be a random polymer or a triblock polymer.
[0052] The random polymers prepared by the living radical polymerization have narrower molecular weight distributions than those prepared by free radical polymerization, and can be obtained in high yields.
[0053] Specific examples of the triblock polymer include: (1) a step of mixing a polymerization component [I] containing a functional group-containing monomer (e.g., functional group-containing monomer (a2)) and a non-functional group-containing monomer (e.g., alkyl(meth)acrylate (a1)) and a RAFT agent in a reaction solvent, and adding a radical polymerization initiator to polymerize the polymerization component [I] to obtain a polymer segment (Y)-(Y) having a functional group; (2) a step of polymerizing the polymer segment (Y)-(Y) obtained in the above step with the remaining polymerization component [II] in the presence of a RAFT agent as a polymerization initiator to link the polymer segment (Y) to produce a polymer segment (Z), thereby producing an acrylic resin (A) having a structure of (Y)-(Z)-(Y); It is preferable to produce it by the following method.
[0054] [RAFT Agents (Chain Transfer Agents)] As the RAFT agent used in the living radical polymerization, a conventionally known compound can be used, and for example, a thiocarbonylthio compound such as a trithiocarbonyl, dithiocarbonyl, dithioester, or xanthate can be used.
[0055] Among the RAFT agents, for random polymers, for example, trithiocarbonyl-based 3-((((1-carboxyethyl)thio)carbonothioyl)thio)propanoic acid, bis[4-(methoxycarbonyl)benzyl]trithiocarbonate, trithiocarbonic acid bis[[4-[[ethyl-(2-acetoxyethyl)amino]carbonyl]phenyl]methyl] ester, and trithiocarbonic acid bis[[4-[[ethyl-(2-hydroxyethyl)amino]carbonyl]phenyl]methyl] ester are preferred.
[0056] Among the RAFT agents, trithiocarbonyl-based RAFT agents are preferred for triblock polymers because they enable the production of the polymer segments (Y)-(Y), which correspond to both ends of the acrylic resin, in a single step, and because they are less likely to delay polymerization and less susceptible to hydrolysis, resulting in excellent production efficiency. Particularly preferred are bis[4-(methoxycarbonyl)benzyl]trithiocarbonate, trithiocarbonate bis[[4-[[ethyl-(2-acetoxyethyl)amino]carbonyl]phenyl]methyl]ester, and trithiocarbonate bis[[4-[[ethyl-(2-hydroxyethyl)amino]carbonyl]phenyl]methyl]ester.
[0057] The glass transition temperature (Tg) of the acrylic resin (A) thus obtained is preferably −60 to 0° C., particularly −55 to −10° C., and further preferably −52 to −20° C. If the glass transition temperature is too high, the adhesiveness tends to decrease, whereas if it is too low, the contamination of the workpiece tends to increase.
[0058] The glass transition temperature (Tg) is a value calculated by applying the glass transition temperature and mass fraction of each of the monomers constituting the acrylic resin (A) as a homopolymer to the following Fox's formula.
[0059]
number
[0060] Here, the glass transition temperature when the monomers constituting the acrylic resin (A) are made into a homopolymer is usually measured by a differential scanning calorimeter (DSC), and can be measured by a method in accordance with JIS K 7121-1987 or JIS K 6240.
[0061] The weight-average molecular weight of the acrylic resin (A) is usually 100,000 to 3,000,000, preferably 150,000 to 2,500,000, particularly preferably 200,000 to 2,000,000, and especially preferably 300,000 to 1,800,000. If the weight-average molecular weight is too small, the material tends to be more susceptible to contamination, whereas if it is too large, the coating properties tend to be poor and there is also a tendency for this to be disadvantageous in terms of cost.
[0062] Furthermore, the dispersity (weight average molecular weight / number average molecular weight) of the acrylic resin (A) is preferably 20 or less, particularly preferably 10 or less, even more preferably 7 or less, and especially preferably 6 or less. If the dispersity is too high, contamination of the workpiece tends to increase. The lower limit of the dispersity is usually 1.1 in view of production limitations.
[0063] The weight-average molecular weight of the acrylic resin (A) is a weight-average molecular weight converted into a standard polystyrene molecular weight. The weight-average molecular weight was measured using a high-performance liquid chromatograph (Waters Japan, "Waters 2695 (main body)" and "Waters 2414 (detector)") with a column: Shodex GPC KF-806L (exclusion limit molecular weight: 2 × 10 7 Separation range: 100 to 2 × 10 7The number average molecular weight can be measured by using three columns in series (theoretical plate number: 10,000 / column, filler material: styrene-divinylbenzene copolymer, filler particle size: 10 μm), and the number average molecular weight can also be obtained in the same way.
[0064] The viscosity of the acrylic resin (A) solution at 25°C is preferably 5 to 20,000 mPa·s, and more preferably 100 to 10,000 mPa·s. If the viscosity is outside this range, the coating properties tend to decrease. The viscosity is measured using a Brookfield viscometer (rotor 3M, rotation speed 6 rpm).
[0065] [Urethane (meth)acrylate compound (B)] In order to exhibit active energy ray curability when irradiated with active energy rays, the pressure-sensitive adhesive composition preferably contains a urethane (meth)acrylate compound (B). The urethane (meth)acrylate compound (B) is a compound having a urethane bond and a (meth)acryloyl group.
[0066] The urethane (meth)acrylate compound (B) may be a urethane (meth)acrylate compound (B1) which is a reaction product of a hydroxyl group-containing (meth)acrylate compound (b1) and a polyvalent isocyanate compound (b2), or a urethane (meth)acrylate compound (B2) which is a reaction product of a hydroxyl group-containing (meth)acrylate compound (b1), a polyvalent isocyanate compound (b2), and a polyol compound (b3). The urethane (meth)acrylate compound (B) may be used alone or in combination of two or more.
[0067] The hydroxyl group-containing (meth)acrylate compound (b1) is preferably one having one hydroxyl group, and examples thereof include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate, 2-hydroxyethyl acryloyl phosphate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, caprolactone-modified 2-hydroxyethyl (meth)acrylate, dipropylene glycol (meth)acrylate, fatty acid-modified glycidyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and 2-hydroxy-3-(meth)acrylate. Examples of the hydroxyl group-containing (meth)acrylate compounds include those containing one ethylenically unsaturated group, such as aryloyloxypropyl (meth)acrylate; those containing two ethylenically unsaturated groups, such as glycerin di(meth)acrylate and 2-hydroxy-3-acryloyloxypropyl methacrylate; and those containing three or more ethylenically unsaturated groups, such as pentaerythritol tri(meth)acrylate, caprolactone-modified pentaerythritol tri(meth)acrylate, ethylene oxide-modified pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, caprolactone-modified dipentaerythritol penta(meth)acrylate, and ethylene oxide-modified dipentaerythritol penta(meth)acrylate. The hydroxyl group-containing (meth)acrylate compounds (b1) can be used alone or in combination of two or more.
[0068] Among these, hydroxyl group-containing (meth)acrylate compounds containing three or more ethylenically unsaturated groups are preferred because of their excellent curability after irradiation with active energy rays, and pentaerythritol tri(meth)acrylate and dipentaerythritol penta(meth)acrylate are particularly preferred.
[0069] Examples of the polyisocyanate compound (b2) include aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, polyphenylmethane polyisocyanate, modified diphenylmethane diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate; hexamethylene diisocyanate, and trimethylhexamethylene diisocyanate. aliphatic polyisocyanates such as hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, and norbornene diisocyanate; alicyclic polyisocyanates such as hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, and norbornene diisocyanate; or isocyanurates or polymeric compounds of these polyisocyanates, allophanate polyisocyanates, biuret polyisocyanates, and water-dispersible polyisocyanates. These may be used alone or in combination of two or more.
[0070] Among these, aromatic polyisocyanates such as tolylene diisocyanate, aliphatic diisocyanates such as hexamethylene diisocyanate and trimethylhexamethylene diisocyanate, and alicyclic diisocyanates such as hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate and norbornene diisocyanate are preferred, from the viewpoint of excellent reactivity and versatility, and tolylene diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate and hexamethylene diisocyanate are particularly preferred, and tolylene diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate are even more preferred.
[0071] The polyol compound (b3) may be any compound containing two or more hydroxyl groups, and examples thereof include aliphatic polyols, alicyclic polyols, polyether polyols, polyester polyols, polycarbonate polyols, polyolefin polyols, polybutadiene polyols, polyisoprene polyols, (meth)acrylic polyols, polysiloxane polyols, etc. These may be used alone or in combination of two or more.
[0072] Examples of the aliphatic polyol include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, trimethylene glycol, dimethylolpropane, neopentyl glycol, 2,2-diethyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,4-tetramethylenediol, 1,3-tetramethylenediol, 2-methyl-1,3-trimethylenediol, 1,5-pentamethylenediol, 1 Examples of suitable hydroxyl groups include aliphatic alcohols containing two hydroxyl groups such as 1,6-hexamethylenediol, 3-methyl-1,5-pentamethylenediol, 2,4-diethyl-1,5-pentamethylenediol, pentaerythritol diacrylate, 1,9-nonanediol, and 2-methyl-1,8-octanediol; sugar alcohols such as xylitol and sorbitol; and aliphatic alcohols containing three or more hydroxyl groups such as glycerin, trimethylolpropane, and trimethylolethane.
[0073] Examples of the alicyclic polyol include cyclohexanediols such as 1,4-cyclohexanediol and cyclohexyldimethanol, hydrogenated bisphenols such as hydrogenated bisphenol A, and tricyclodecane dimethanol.
[0074] Examples of the polyether polyols include alkylene structure-containing polyether polyols such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polybutylene glycol, polypentamethylene glycol, and polyhexamethylene glycol, as well as random or block copolymers of these polyalkylene glycols.
[0075] Examples of the polyester polyol include a condensation polymer of a polyhydric alcohol and a polycarboxylic acid; a ring-opening polymer of a cyclic ester (lactone); and a reaction product of three components: a polyhydric alcohol, a polycarboxylic acid, and a cyclic ester.
[0076] Examples of the polyhydric alcohol include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, trimethylene glycol, 1,4-tetramethylene diol, 1,3-tetramethylene diol, 2-methyl-1,3-trimethylene diol, 1,5-pentamethylene diol, neopentyl glycol, 1,6-hexamethylene diol, 3-methyl-1,5-pentamethylene diol, 2,4-diethyl-1,5-pentamethylene diol, glycerin, trimethylolpropane, trimethylolethane, cyclohexanediols (such as 1,4-cyclohexanediol), bisphenols (such as bisphenol A), and sugar alcohols (such as xylitol and sorbitol). Examples of the polycarboxylic acid include aliphatic dicarboxylic acids such as malonic acid, maleic acid, fumaric acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid; and aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, orthophthalic acid, 2,6-naphthalenedicarboxylic acid, paraphenylenedicarboxylic acid, and trimellitic acid. Examples of the cyclic ester include propiolactone, β-methyl-δ-valerolactone, and ε-caprolactone.
[0077] Examples of the polycarbonate polyol include a reaction product of a polyhydric alcohol with phosgene, a ring-opening polymerization product of a cyclic carbonate ester (such as an alkylene carbonate), etc. Examples of the polyhydric alcohol include the polyhydric alcohols exemplified in the description of the polyester polyol, and examples of the alkylene carbonate include ethylene carbonate, trimethylene carbonate, tetramethylene carbonate, hexamethylene carbonate, etc. The polycarbonate polyol may be any compound having a carbonate bond in the molecule and a hydroxyl group at the end, and may have an ester bond in addition to the carbonate bond.
[0078] The polyolefin polyols include those having a homopolymer or copolymer of ethylene, propylene, butene, or the like as a saturated hydrocarbon skeleton and having hydroxyl groups at the molecular terminals.
[0079] The polybutadiene-based polyols include those having a butadiene copolymer as a hydrocarbon skeleton and having hydroxyl groups at the molecular terminals. The polybutadiene polyol may be a hydrogenated polybutadiene polyol in which all or part of the ethylenically unsaturated groups contained in the structure thereof have been hydrogenated.
[0080] The polyisoprene-based polyols include those having a copolymer of isoprene as a hydrocarbon skeleton and having hydroxyl groups at the molecular terminals. The polyisoprene-based polyol may be a hydrogenated polyisoprene polyol in which all or part of the ethylenically unsaturated groups contained in the structure thereof have been hydrogenated.
[0081] The (meth)acrylic polyol includes a (meth)acrylic acid ester polymer or copolymer having at least two hydroxy groups in the molecule. Examples of such a (meth)acrylic acid ester include (meth)acrylic acid alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, and octadecyl (meth)acrylate.
[0082] Examples of the polysiloxane polyol include dimethylpolysiloxane polyol and methylphenylpolysiloxane polyol.
[0083] Among these, aliphatic polyols and alicyclic polyols are preferably used, and from the viewpoint of versatility, polyester polyols, polyether polyols and polycarbonate polyols are preferably used.
[0084] The weight-average molecular weight of the polyol compound (b3) is preferably 60 to 5,000, particularly preferably 100 to 3,000, and even more preferably 150 to 2,000. If the weight-average molecular weight of the polyol compound (b3) is too large, the resulting urethane (meth)acrylate compound (B2) and acrylic resin (A) tend to be difficult to mix uniformly, which tends to result in adhesive residue on the workpiece. If the weight-average molecular weight of the polyol compound (b3) is too small, cracks tend to occur in the pressure-sensitive adhesive layer after irradiation with active energy rays.
[0085] The urethane (meth)acrylate compound (B) is preferably a reaction product of a hydroxyl group-containing (meth)acrylate compound containing three or more ethylenically unsaturated groups in the molecule and a polyvalent isocyanate compound (b2).
[0086] The urethane (meth)acrylate compound (B) can be produced by reacting the above-mentioned components by known reaction means. In general, in the case of the urethane (meth)acrylate compound (B1), the hydroxyl group-containing (meth)acrylate compound (b1) and the polyvalent isocyanate compound (b2), and in the case of the urethane (meth)acrylate compound (B2), the polyol compound (b3) are also charged into a reactor all at once or separately, and the urethane (meth)acrylate compound (B2) can be produced by carrying out a urethanization reaction by a known reaction means. In addition, in the case of producing the urethane (meth)acrylate compound (B2), a method of reacting the polyol compound (b3) with the polyvalent isocyanate compound (b2) in advance, and then reacting the resulting reaction product with the hydroxyl group-containing (meth)acrylate compound (b1), is useful in terms of the stability of the urethanization reaction and the reduction of by-products.
[0087] In the reaction between the hydroxyl group-containing (meth)acrylate compound (b1) and the polyvalent isocyanate compound (b2), it is preferable to use a reaction catalyst in order to promote the reaction.
[0088] Examples of the reaction catalyst include organic metal compounds such as dibutyltin dilaurate, trimethyltin hydroxide, and tetra-n-butyltin; metal salts such as zinc octenoate, tin octenoate, tin octoate, cobalt naphthenate, stannous chloride, and stannic chloride; amine catalysts such as triethylamine, benzyldiethylamine, 1,4-diazabicyclo[2,2,2]octane, 1,8-diazabicyclo[5,4,0]undecene, N,N,N',N'-tetramethyl-1,3-butanediamine, and N-ethylmorpholine; bismuth nitrate, bismuth bromide, bismuth iodide, and bismuth sulfide; organic bismuth compounds such as dibutyl bismuth dilaurate and dioctyl bismuth dilaurate; and 2-ethylhexyl bismuth compounds. Examples of suitable catalysts include bismuth catalysts such as organic acid bismuth salts (e.g., bismuth xanate, bismuth naphthenate, bismuth isodecanoate, bismuth neodecanoate, bismuth laurate, bismuth maleate, bismuth stearate, bismuth oleate, bismuth linoleate, bismuth acetate, bismuth bisneodecanoate, bismuth disalicylate, and bismuth digallate); zirconium catalysts (e.g., inorganic zirconium, organic zirconium, and simple zirconium); and catalysts containing two or more catalysts, such as zinc 2-ethylhexanoate / zirconium tetraacetylacetonate. Among these catalysts, dibutyltin dilaurate and 1,8-diazabicyclo[5.4.0]undecene are preferred. These catalysts can be used singly or in combination. Among these, dibutyltin dilaurate and 1,8-diazabicyclo[5.4.0]undecene are preferred.
[0089] In the urethanization reaction, organic solvents that do not have a functional group that reacts with an isocyanate group, such as esters such as ethyl acetate and butyl acetate, ketones such as methyl ethyl ketone and methyl isobutyl ketone, and aromatics such as toluene and xylene, can be used.
[0090] The reaction temperature is usually 30 to 90°C, preferably 40 to 80°C, and the reaction time is usually 2 to 10 hours, preferably 3 to 8 hours.
[0091] The urethane-forming reaction is terminated when the content of residual isocyanate groups in the reaction system reaches 0.5% by mass or less, thereby obtaining the urethane (meth)acrylate compound (B).
[0092] The urethane (meth)acrylate compound (B) thus obtained preferably has 5 to 20 ethylenically unsaturated groups, more preferably 5 to 18, and particularly preferably 6 to 15, from the viewpoint of releasability after irradiation with active energy rays. If the number of ethylenically unsaturated groups is too large, the crosslinking density after irradiation with active energy rays becomes too high, making the pressure-sensitive adhesive layer more susceptible to cracking, whereas if the number is too small, sufficient crosslinking density cannot be obtained, making peeling after irradiation with active energy rays more difficult.
[0093] The weight-average molecular weight of the urethane (meth)acrylate compound (B) is usually 500 to 10,000, preferably 750 to 5,000, and more preferably 1,000 to 4,000. If the weight-average molecular weight is too large, the viscosity of the urethane (meth)acrylate compound (B) increases, the compatibility with the acrylic resin (A) decreases, and adhesive residue tends to be more likely to be left on the workpiece. If the weight-average molecular weight is too small, the urethane (meth)acrylate compound (B) tends to bleed from the pressure-sensitive adhesive sheet, making adhesive residue more likely to be left.
[0094] The weight-average molecular weight of the urethane (meth)acrylate compound (B) is a weight-average molecular weight converted into a standard polystyrene molecular weight, and is measured using a high-performance liquid chromatograph (Waters, "ACQUITY APC System") equipped with four columns arranged in series: one ACQUITY APC XT 450, one ACQUITY APC XT 200, and two ACQUITY APC XT 45.
[0095] The viscosity of the urethane (meth)acrylate compound (B) used in the present invention at 60°C is preferably 500 to 100,000 mPa·s, and particularly preferably 1,000 to 50,000 mPa·s. If the viscosity is outside this range, the coatability tends to decrease. The viscosity can be measured using an E-type viscometer.
[0096] The content of the urethane (meth)acrylate compound (B) is usually 20 to 200 parts by mass, preferably 25 to 150 parts by mass, and particularly preferably 30 to 100 parts by mass, relative to 100 parts by mass of the acrylic resin (A). If the content of the urethane (meth)acrylate compound (B) is too low, the releasability after irradiation with active energy rays tends to be easily reduced, while if it is too high, cracks tend to be easily generated in the pressure-sensitive adhesive layer after irradiation with active energy rays.
[0097] [Polymerization inhibitor (C)] In the present pressure-sensitive adhesive composition, the polymerization inhibitor (C) contains a nitroso compound (C1). When the acrylic resin (A) is exposed to high temperatures, it generates alkyl radicals, which then react with oxygen to generate peroxy radicals. These peroxy radicals abstract hydrogen from the acrylic resin (A) to generate the next alkyl radical, which itself becomes a hydroperoxide. The hydroperoxide then decomposes, generating new radicals, which accelerates the degradation of the acrylic resin (A). Furthermore, since active energy ray-curable peel-type pressure-sensitive adhesive compositions are generally cured by radicals, there is also the problem that curing proceeds due to heat before being cured by active energy rays. In the present invention, the use of a nitroso compound (C1) as the polymerization inhibitor (C) stabilizes alkyl radicals, inhibits deterioration of the acrylic resin (A), and further inhibits curing due to alkyl radicals, thereby achieving the effects of the present invention.
[0098] Examples of the nitroso compound (C1) include aromatic nitroso compounds such as nitrosobenzene, 2-nitrosotoluene, 1,2,4,5-tetramethyl-3-nitrosobenzene, 4-nitrosophenol, 1-nitroso-2-naphthol, 2-nitroso-1-naphthol, 4-nitrosodiphenylamine, 3,5-dibromo-4-nitrosobenzenesulfonic acid, Nt-butyl-N-nitrosoaniline, ammonium N-nitrosophenylhydroxylamine, and N-nitrosophenylhydroxylamine aluminum salt; heterocyclic nitroso compounds such as N-nitrosopyrrolidine, 1-nitrosopiperidine, and 4-nitrosomorpholine; and aliphatic nitroso compounds such as N-nitrosodimethylamine, N-nitrosodiethylamine, N-nitroso-N-methylbutylamine, N-nitroso-N-ethylurea, and N-nitrosohexamethyleneimine. These compounds may be used alone or in combination of two or more. Among these, from the viewpoint of compatibility, aromatic nitroso compounds are preferred, ammonium N-nitrosophenylhydroxylamine and / or N-nitrosophenylhydroxylamine aluminum salt are more preferred, and N-nitrosophenylhydroxylamine aluminum salt is particularly preferred.
[0099] The polymerization inhibitor (C) may contain a polymerization inhibitor other than the nitroso compound (C1).
[0100] Examples of polymerization inhibitors other than the nitroso compound (C1) include dihydric phenols such as hydroquinone, catechol, and resorcinol, benzoquinones such as 1,4-benzoquinone, phenothiazine, and copper dimethyldithiocarbamate.
[0101] The content of the polymerization inhibitor (C) is usually preferably 0.001 to 3 parts by mass, particularly preferably 0.01 to 2 parts by mass, and even more preferably 0.05 to 1 part by mass, relative to 100 parts by mass of the acrylic resin (A). If the amount of the polymerization inhibitor (C) is too small, the reduction in adhesive strength after heating and irradiation with active energy rays tends to be insufficient, while if the amount is too large, radicals generated from the photoinitiator upon irradiation with active energy rays tend to be trapped, resulting in an insufficient reduction in adhesive strength after irradiation with active energy rays.
[0102] The content of the nitroso compound (C1) is usually 0.01 to 1 part by mass, preferably 0.05 to 0.8 parts by mass, and particularly preferably 0.1 to 0.5 parts by mass, based on 100 parts by mass of the acrylic resin (A).
[0103] The content of the nitroso compound (C1) is usually 0.01 to 10 parts by mass, preferably 0.1 to 5 parts by mass, and more preferably 0.2 to 1 part by mass, based on 100 parts by mass of the urethane (meth)acrylate compound (B).
[0104] Furthermore, the mass ratio of the nitroso compound (C) to the photopolymerization initiator (E) described below [nitroso compound (C1) / photopolymerization initiator (E)] is usually 1 / 50, preferably 1 / 20.
[0105] By setting the content of the nitroso compound (C1) within the above range, excellent heat resistance can be obtained. If the content of the nitroso compound (C1) is too small, the adhesive strength after heating and irradiation with active energy rays tends to be insufficiently reduced, while if the content is too large, radicals generated from the photopolymerization initiator upon irradiation with active energy rays tend to be trapped, resulting in an insufficient reduction in adhesive strength after irradiation with active energy rays.
[0106] Furthermore, the content of the nitroso compound (C1) in the polymerization inhibitor (C) is usually 5% by mass or more, preferably 30% by mass or more, with the upper limit being 100% by mass. Within this range, the effects of the present invention tend to be easily achieved.
[0107] [Crosslinking agent (D)] The present resin composition preferably further contains a crosslinking agent (D) in order to improve the adhesive strength before irradiation with active energy rays. As described above, the crosslinking agent (D) reacts with the functional groups in the acrylic resin (A) to form a crosslinked structure, and examples thereof include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, aziridine-based crosslinking agents, melamine-based crosslinking agents, aldehyde-based crosslinking agents, amine-based crosslinking agents, and metal chelate-based crosslinking agents. Among these, it is preferable to use an isocyanate-based crosslinking agent in terms of improving adhesion to the adherend and reactivity with the acrylic resin (A).
[0108] The isocyanate-based crosslinking agent contains at least two isocyanate groups, and examples thereof include aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, and xylylene diisocyanate, aliphatic polyisocyanates such as hexamethylene diisocyanate, alicyclic polyisocyanates such as isophorone diisocyanate and hydrogenated diphenylmethane diisocyanate, and biuret and isocyanurate forms thereof, as well as adducts which are reaction products with low-molecular-weight active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil. Among these, aromatic polyisocyanates and adducts of aromatic polyisocyanates and trimethylolpropane are preferred in terms of chemical resistance and reactivity with functional groups, and adducts of tolylene diisocyanate and trimethylolpropane are particularly preferred.
[0109] Examples of the epoxy-based crosslinking agent include 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl-m-xylylenediamine, ethylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane diglycidyl ether, diglycidylaniline, and diglycidylamine.
[0110] Examples of the aziridine-based crosslinking agent include diphenylmethane-4,4'-bis(1-aziridinecarboxamide), trimethylolpropane tri-β-aziridinylpropionate, tetramethylolmethane tri-β-aziridinylpropionate, toluene-2,4-bis(1-aziridinecarboxamide), triethylenemelamine, bisisophthaloyl-1-(2-methylaziridine), tris-1-(2-methylaziridine)phosphine, and trimethylolpropane tri-β-(2-methylaziridine)propionate.
[0111] Examples of the melamine-based crosslinking agent include melamine; methylolmelamine derivatives such as amino group-containing methylolmelamine obtained by condensing melamine with formaldehyde, imino group-containing methylolmelamine, and hexamethylolmelamine; and alkylated methylolmelamines such as partially or completely alkylated methylolmelamine and imino group-containing partially or completely alkylated methylolmelamine obtained by reacting a methylolmelamine derivative with a lower alcohol such as methyl alcohol or butyl alcohol to partially or completely etherify the methylolmelamine derivative.
[0112] Examples of the aldehyde crosslinking agent include aldehyde compounds that liberate aldehyde in an aqueous solution, such as formaldehyde, acetaldehyde, propionaldehyde, butylaldehyde, glyoxal, glutaraldehyde, dialdehyde starch, hexamethylenetetramine, 1,4-dioxane-2,3-diol, 1,3-bis(hydroxymethyl)-2-imidazolidine, dimethylol urea, N-methylol acrylamide, urea formalin resin, and melamine formalin resin, as well as aromatic aldehyde compounds such as benzaldehyde, 2-methylbenzaldehyde, 4-methylbenzaldehyde, p-hydroxybenzaldehyde, and m-hydroxybenzaldehyde.
[0113] Examples of the amine-based crosslinking agent include 4,4'-methylene-bis(2-chloroaniline), modified 4,4'-methylene-bis(2-chloroaniline), and diethyltoluenediamine.
[0114] Examples of the metal chelate crosslinking agent include chelate compounds whose metal atom is aluminum, zirconium, titanium, zinc, iron, tin, etc., and aluminum chelate compounds are preferred from the viewpoint of performance. Examples of the aluminum chelate compound include diisopropoxyaluminum monooleyl acetoacetate, monoisopropoxyaluminum bisoleyl acetoacetate, monoisopropoxyaluminum monooleate monoethyl acetoacetate, diisopropoxyaluminum monolauryl acetoacetate, diisopropoxyaluminum monostearyl acetoacetate, diisopropoxyaluminum monoisostearyl acetoacetate, etc.
[0115] The crosslinking agent (D) may be used alone or in combination of two or more kinds.
[0116] The content of the crosslinking agent (D) is usually preferably 0.01 to 20 parts by mass, particularly preferably 0.2 to 10 parts by mass, and even more preferably 0.2 to 3 parts by mass, per 100 parts by mass of the acrylic resin (A). If the amount of crosslinking agent (D) is too small, the cohesive strength of the adhesive will decrease, which will tend to cause adhesive residue, while if the amount is too large, the flexibility and adhesive strength of the adhesive will decrease, which will tend to cause lifting from the workpiece.
[0117] [Photopolymerization initiator (E)] The present resin composition preferably contains a photopolymerization initiator (E). The photopolymerization initiator (E) may be any one that generates radicals by the action of light, and examples thereof include acetophenones such as diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzyl dimethyl ketal, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexyl phenyl ketone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-methyl-2-morpholino(4-thiomethylphenyl)propan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 2-benzyl-2-(dimethylamino)-4'-morpholinobutyrophenone, and 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone oligomer; benzoins such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; benzophenones such as benzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, 2,4,6-trimethylbenzophenone, 4-benzoyl-N,N-dimethyl-N-[2-(1-oxo-2-propenyloxy)ethyl]benzenemethanaminium bromide, and (4-benzoylbenzyl)trimethylammonium chloride; thioxanthones such as 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-dichlorothioxanthone, 1-chloro-4-propoxythioxanthone, and 2-(3-dimethylamino-2-hydroxy)-3,4-dimethyl-9H-thioxanthone-9-one mesochloride; Acylphosphine oxides such as 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide; Among them, acylphosphonoxides are preferred, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide is particularly preferred. These photopolymerization initiators (E) can be used alone or in combination of two or more.
[0118] Furthermore, as an auxiliary agent for these photopolymerization initiators (E), it is also possible to use in combination, for example, triethanolamine, triisopropanolamine, 4,4'-dimethylaminobenzophenone (Michler's ketone), 4,4'-diethylaminobenzophenone, 2-dimethylaminoethylbenzoic acid, ethyl 4-dimethylaminobenzoate, (n-butoxy)ethyl 4-dimethylaminobenzoate, isoamyl 4-dimethylaminobenzoate, 2-ethylhexyl 4-dimethylaminobenzoate, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, etc. These auxiliary agents can be used alone or in combination of two or more.
[0119] The content of the photopolymerization initiator (E) is preferably 0.1 to 20 parts by mass, particularly preferably 0.5 to 15 parts by mass, and particularly preferably 1 to 10 parts by mass, per 100 parts by mass of the total of the acrylic resin (A) and the urethane (meth)acrylate compound (B) (including the ethylenically unsaturated compound when an ethylenically unsaturated compound described below is used). If the content of the photopolymerization initiator (E) is too low, the releasability after irradiation with active energy rays tends to be easily reduced, and if it is too high, the contamination of the workpiece after irradiation with active energy rays tends to be increased.
[0120] [Other ingredients] The present pressure-sensitive adhesive composition may further contain, for example, an ethylenically unsaturated group-containing compound other than the acrylic resin (A) and the urethane (meth)acrylate compound (B), within a range that does not impair the effects of the present invention, in terms of releasability after irradiation with active energy rays. The pressure-sensitive adhesive composition may also contain additives such as antistatic agents, plasticizers, fillers, pigments, diluents, antioxidants, UV absorbers, UV stabilizers, and tackifying resins. These additives may be used alone or in combination of two or more. In addition to the additives, the pressure-sensitive adhesive composition may contain small amounts of impurities contained in the raw materials used to produce the components of the pressure-sensitive adhesive composition.
[0121] [Active energy ray-curable peelable pressure-sensitive adhesive composition] Thus, the present pressure-sensitive adhesive composition is obtained by mixing the acrylic resin (A), the urethane (meth)acrylate compound (B), the polymerization inhibitor (C), preferably the crosslinking agent (D), the photopolymerization initiator (E), and, if necessary, other components. The content of the acrylic resin (A) in the entire pressure-sensitive adhesive composition is usually 30% by mass or more, preferably 35% by mass or more, and particularly preferably 40% by mass or more. If the content is too low, it becomes difficult to obtain the effects of the present invention.
[0122] The present pressure-sensitive adhesive composition is preferably used as a pressure-sensitive adhesive sheet for temporarily protecting the surface of a workpiece when processing the workpiece, such as an electronic substrate, a semiconductor wafer, a processed glass product, a metal plate, a plastic plate, etc. The pressure-sensitive adhesive sheet has a pressure-sensitive adhesive layer in which the pressure-sensitive adhesive composition is crosslinked. The pressure-sensitive adhesive sheet will now be described.
[0123] [Adhesive sheet] A pressure-sensitive adhesive sheet according to one embodiment of the present invention (hereinafter sometimes referred to as "the pressure-sensitive adhesive sheet") typically comprises a substrate sheet, a pressure-sensitive adhesive layer comprising the pressure-sensitive adhesive composition, and a release film. The pressure-sensitive adhesive sheet can be produced by first coating the pressure-sensitive adhesive composition, either as is or after adjusting its concentration with an appropriate organic solvent, directly onto a release film or a substrate sheet. The composition is then dried, for example, by heat treatment at 80 to 105°C for 0.5 to 10 minutes, and then attached to a substrate sheet or a release film to obtain the pressure-sensitive adhesive sheet. Furthermore, in order to balance the adhesive properties, further aging may be performed after drying.
[0124] Examples of the substrate sheet include sheets made of at least one synthetic resin selected from the group consisting of polyester resins such as polyethylene naphthalate, polyethylene terephthalate, polybutylene terephthalate, and polyethylene terephthalate / isophthalate copolymer; polyolefin resins such as polyethylene, polypropylene, and polymethylpentene; polyethylene fluoride resins such as polyvinyl fluoride, polyvinylidene fluoride, and polyethylene fluoride; polyamides such as nylon 6 and nylon 6,6; vinyl polymers such as polyvinyl chloride, polyvinyl chloride / vinyl acetate copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polyvinyl alcohol, and vinylon; cellulose resins such as cellulose triacetate and cellophane; acrylic resins such as polymethyl methacrylate, polyethyl methacrylate, polyethyl acrylate, and polybutyl acrylate; polystyrene; polycarbonate; polyarylate; and polyimide; metal foils such as aluminum, copper, and iron; paper such as fine paper and glassine paper; and woven and nonwoven fabrics made of glass fiber, natural fibers, synthetic fibers, and the like. These substrate sheets can be used as a single layer or as a multi-layered body in which two or more types are laminated together. Among these, sheets made of synthetic resins are preferred from the viewpoint of weight reduction and the like.
[0125] Furthermore, as the release film, for example, various synthetic resin sheets, paper, woven fabrics, nonwoven fabrics, etc. exemplified above as the base material sheets can be used which have been subjected to a release treatment.
[0126] The method for applying the pressure-sensitive adhesive composition is not particularly limited as long as it is a common coating method, and examples thereof include roll coating, die coating, gravure coating, comma coating, and screen printing.
[0127] The thickness of the pressure-sensitive adhesive layer of the present pressure-sensitive adhesive sheet is generally preferably 3 to 200 μm, and more preferably 5 to 100 μm.
[0128] The aging conditions are typically a temperature of room temperature (23°C) to 70°C, and a time of 1 to 30 days. Specifically, the aging may be performed under conditions such as 1 to 20 days at 23°C, 3 to 10 days at 23°C, or 1 to 7 days at 40°C.
[0129] The gel fraction of the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet is preferably 10 to 99% from the viewpoint of adhesiveness, particularly preferably 20 to 97%, and even more preferably 40 to 95%. If the gel fraction is too low, the adhesive strength to the workpiece tends to decrease, while if the gel fraction is too high, the adhesive strength to the workpiece tends to decrease.
[0130] The gel fraction is a measure of the degree of crosslinking (degree of hardening) and is calculated, for example, by the following method: The pressure-sensitive adhesive sheet is attached to a SUS mesh sheet (200 mesh), the pressure-sensitive adhesive sheet is wrapped, and then the sheet is immersed in ethyl acetate in a sealed container for 24 hours. The gel fraction is calculated from the change in mass of the pressure-sensitive adhesive layer before and after immersion in ethyl acetate using the following formula. Gel fraction (%) = mass (g) of the adhesive layer after immersion in ethyl acetate / Weight of adhesive layer before immersion in ethyl acetate (g) x 100
[0131] The gel fraction of the pressure-sensitive adhesive layer can be adjusted to fall within the above range by adjusting the type and amount of the crosslinking agent (D), for example.
[0132] When the adhesive layer of the present adhesive sheet is irradiated with active energy rays, the ethylenically unsaturated groups contained in the adhesive layer are polymerized, causing the adhesive layer to harden and reduce its adhesive strength, thereby enabling it to be peeled off.
[0133] As the active energy ray, generally, light rays such as far ultraviolet rays, ultraviolet rays, near ultraviolet rays, infrared rays, electromagnetic waves such as X-rays and gamma rays, as well as electron beams, proton beams, neutron beams, etc. can be used. However, ultraviolet rays are preferred in terms of curing speed, ease of availability of irradiation equipment, cost, etc.
[0134] The cumulative irradiation dose of the ultraviolet light is usually 50 to 3000 mJ / cm 2 , preferably 100 to 1,000 mJ / cm 2 The irradiation time varies depending on the type of light source, the distance between the light source and the adhesive layer, the thickness of the adhesive layer, and other conditions, but is usually several seconds, and in some cases may be a fraction of a second.
[0135] The adhesive strength of the present pressure-sensitive adhesive sheet varies depending on the type of substrate sheet, the type of workpiece, etc., but is preferably 3.0 N / 25 mm or more, more preferably 4.0 N / 25 mm or more, before irradiation with active energy rays. The upper limit of the adhesive strength before irradiation with active energy rays is usually 100 N / 25 mm. The adhesive strength after irradiation with active energy rays is preferably 0.5 N / 25 mm or less, and more preferably 0.1 N / 25 mm or less. The adhesive strength is measured, for example, by cutting the adhesive sheet into a size of 25 mm x 100 mm and applying pressure to the adhesive layer by rolling a rubber roller weighing 2 kg back and forth twice on a soda glass plate in an atmosphere of 23°C and 50% RH.
[0136] Based on the above measurement conditions, the adhesive strength of the present pressure-sensitive adhesive sheet after heating at 180° C. for 1 hour is preferably 3.0 N / 25 mm or more, and more preferably 10.0 N / 25 mm or more. Furthermore, after that, ultraviolet irradiation (cumulative irradiation amount 180 mJ / cm 2The adhesive strength when the adhesive tape is applied is preferably less than 1.5 N / 25 mm, and more preferably less than 1.0 N / 25 mm. In addition, it is preferable that the adhesive tape can be peeled from the adherend interface without leaving any adhesive residue or traces.
[0137] The present adhesive composition is useful as a peel-type adhesive sheet, for example, by laminating an adhesive sheet using the composition as an adhesive layer to a workpiece, temporarily protecting the surface of the workpiece, and then irradiating it with active energy rays, which hardens the adhesive layer and reduces the adhesive strength, allowing it to be easily peeled off from the workpiece. Furthermore, since the adhesive sheet of the present invention has excellent heat resistance, even when subjected to a heating process at, for example, 180°C or higher after being attached to the surface of the workpiece, a drastic decrease in adhesive strength is suppressed, and by subsequent irradiation with active energy rays, the adhesive strength is reduced and excellent peelability is achieved without leaving any adhesive residue. [Example]
[0138] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention. Note that "%" and "parts" below are based on mass.
[0139] [Production of acrylic resin (A-1)] A four-necked round-bottom flask equipped with a reflux condenser, a stirrer, a nitrogen gas inlet, and a thermometer was charged with 118 parts of ethyl acetate. The internal temperature was raised to the boiling point, and a mixture of 54.8 parts of n-butyl acrylate (BA), 40 parts of methyl acrylate (MA), 5 parts of 2-hydroxyethyl acrylate (HEA), 0.2 parts of acrylic acid (Aac), and 0.056 parts of azobisisobutyronitrile (AIBN) as a polymerization initiator was added dropwise over 2 hours. After an additional hour of reaction, 4 parts of an ethyl acetate solution containing 0.037 parts of AIBN was added and the mixture was allowed to react at reflux for 2 hours. Another 4 parts of an ethyl acetate solution containing 0.026 parts of AIBN was added and the mixture was allowed to react at reflux for 2 hours. The reaction was then stopped, and 40 parts of ethyl acetate was added to dilute the mixture to obtain an acrylic resin (A-1). The copolymerization components and physical properties of the resulting acrylic resin (A-1) are shown in Table 1 below.
[0140] [Production of acrylic resin (A-2)] A four-necked round-bottom flask equipped with a reflux condenser, a stirrer, a nitrogen gas inlet, and a thermometer was charged with 118 parts of ethyl acetate, and the internal temperature was raised to the boiling point. A mixture of 58.8 parts of n-butyl acrylate (BA), 40 parts of methyl acrylate (MA), 1 part of 2-hydroxyethyl acrylate (HEA), 0.2 parts of N,N-dimethylaminoethyl acrylate (DMAEA), and 0.056 parts of azobisisobutyronitrile (AIBN) as a polymerization initiator was added dropwise over 2 hours to react. After the reaction was continued for another hour after the completion of the dropwise addition, 4 parts of an ethyl acetate solution containing 0.037 parts of AIBN was added, and the mixture was then reacted at reflux temperature for 2 hours. After that, 4 parts of an ethyl acetate solution containing 0.026 parts of AIBN was added again, and the mixture was reacted at reflux temperature for 2 hours. The reaction was stopped, and 40 parts of ethyl acetate was added to dilute the mixture to obtain an acrylic resin (A-2) solution. The copolymerization components and physical properties of the resulting acrylic resin (A-2) are shown in Table 1 below.
[0141] [Production of acrylic resin (A-3)] A four-necked round-bottom flask equipped with a reflux condenser, a stirrer, a nitrogen gas inlet, and a thermometer was charged with 67.5 parts of ethyl acetate, 13.5 parts of acetone, 76 parts of n-butyl acrylate (BA), 20 parts of methyl acrylate (MA), 4 parts of 4-hydroxybutyl acrylate (4-HBA), and 0.013 parts of azobisisobutyronitrile (AIBN) as a polymerization initiator. The internal temperature was raised to the boiling point and refluxed for 30 minutes. 30 parts of an ethyl acetate solution containing 0.013 parts of AIBN was then added dropwise over 1 hour to allow the reaction to proceed. The reaction was then continued for another 15 minutes after the completion of the addition, and then 30 parts of the ethyl acetate solution was added dropwise over 1 hour to allow the reaction to proceed. After the reaction was continued for 30 minutes at reflux temperature, the reaction was stopped, and the mixture was diluted with 238 parts of ethyl acetate and 0.006 parts of 4-methoxyphenol (MEHQ) to obtain an acrylic resin (A-3) solution. The copolymerization components and physical properties of the resulting acrylic resin (A-3) are shown in Table 1 below.
[0142] [Table 1]
[0143] [Production of urethane (meth)acrylate compound (B-1)] A four-neck flask equipped with a temperature controller, a thermometer, a stirrer, a water-cooled condenser, and a nitrogen gas inlet was charged with 6.6 g of isophorone diisocyanate (isocyanate group content 37.8%), 93.4 g of a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (hydroxyl value 48 mgKOH / g), 0.06 g of 2,6-di-tert-butylcresol as a polymerization inhibitor, and 0.02 g of dibutyltin dilaurate as a reaction catalyst, and the mixture was reacted at 60°C. The reaction was terminated when the residual isocyanate groups reached 0.3% or less, yielding a urethane acrylate compound (B-1) (10 ethylenically unsaturated groups, weight-average molecular weight 2000, acryloyl group concentration 5.0 mmol / g).
[0144] [Production of urethane (meth)acrylate compound (B-2)] A four-neck flask equipped with a temperature controller, a thermometer, a stirrer, a water-cooled condenser, and a nitrogen gas inlet was charged with 18.3 parts of isophorone diisocyanate (isocyanate group content 37.8%), 81.7 parts of a mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate (hydroxyl value 119.1 mg KOH / g), 0.04 parts of 2,6-di-tert-butylcresol as a polymerization inhibitor, and 0.02 parts of dibutyltin dilaurate, a tin compound, as a reaction catalyst, and reacted at 60°C. The reaction was terminated when the residual isocyanate groups reached 0.3% or less, yielding a urethane acrylate compound (B-2) (six ethylenically unsaturated groups, weight-average molecular weight 1300, acryloyl group concentration 25.4 mmol / g).
[0145] [Polymerization inhibitor (C)] The following was prepared as the polymerization inhibitor (C). Polymerization inhibitor (C1-1): Q1301 (N-nitrosophenylhydroxylamine aluminum salt, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Polymerization inhibitor (C-1): MEHQ (4-methoxyphenol, manufactured by Kishida Chemical Co., Ltd.) Polymerization inhibitor (C-2): BHT (dibutylhydroxytoluene, manufactured by Kishida Chemical Co., Ltd.)
[0146] [Crosslinking agent (D)] The following crosslinking agent (D) was prepared: Crosslinking agent (D-1): Takenate D101E (adduct of tolylene diisocyanate and trimethylolpropane, manufactured by Mitsui Chemicals)
[0147] [Photopolymerization initiator (E)] The following photopolymerization initiator (E) was prepared. Photopolymerization initiator (E-1): Omnirad819 (bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, manufactured by IGM Resins BV)
[0148] [Examples 1 to 13, Comparative Examples 1 to 7] To 100 parts of the acrylic resin (A) prepared as described above, a urethane (meth)acrylate compound (B), a polymerization inhibitor (C), a crosslinking agent (D), and a photopolymerization initiator (E) were added and mixed according to the following Table 2, and the solid content concentration (resin content) was adjusted with ethyl acetate to obtain active energy ray-curable peel-type pressure-sensitive adhesive composition solutions of Examples 1 to 13 and Comparative Examples 1 to 7.
[0149] [Table 2]
[0150] The active energy ray-curable release-type pressure-sensitive adhesive composition solutions obtained above in Examples 1 to 13 and Comparative Examples 1 to 7 were applied to a polyester sheet (50 μm thick) [Lumirror® X10S, manufactured by Toray Industries, Inc.] so that the dried thickness was 25 μm. After drying at 100°C for 5 minutes, the sheet was laminated to a 38 μm light-release polyester release sheet (Separator SP-PET® SP01-38BU, manufactured by Mitsui Chemicals Tocello, Inc.) and aged for 3 days in a 40°C environment to obtain a pressure-sensitive adhesive sheet (S1) for measuring adhesive strength. The gel fraction and adhesive strength of the obtained pressure-sensitive adhesive sheet (S1) were measured and evaluated using the methods described below. The evaluation results are shown in Table 3.
[0151] [Gel fraction] The pressure-sensitive adhesive sheet (S1) was cut to 40 mm x 40 mm, the 38 μm polyester release sheet with a light release property was peeled off, and the pressure-sensitive adhesive layer side was attached to a 50 mm x 100 mm SUS mesh sheet (200 mesh). The SUS mesh sheet was folded back from the center in the longitudinal direction to encase the sample. The sample was immersed in a sealed container containing 250 g of ethyl acetate for 24 hours, and the gel fraction was calculated from the change in mass of the pressure-sensitive adhesive layer before and after immersion in ethyl acetate using the following formula. Gel fraction (%) = (mass (g) of the PSA sheet after immersion in ethyl acetate) - X / Mass of adhesive sheet before immersion in ethyl acetate (g) - X) x 100 X = Average mass (g) of seven 40mm x 40mm polyester sheets (50μm thick) [Lumirror (registered trademark) X10S manufactured by Toray Industries, Inc.] cut into sheets.
[0152] [Adhesive strength at 23°C before exposure to active energy rays] A 25 mm x 100 mm test piece was prepared from the pressure-sensitive adhesive sheet (S1), and the 38 μm polyester release sheet with a light release property was peeled off. The test piece was then pressed onto a soda glass plate (manufactured by Nippon Test Panel Co., Ltd.) using a 2 kg rubber roller, which was rolled back and forth twice under pressure in an atmosphere of 23°C and 50% RH. After leaving the test piece to stand in the same atmosphere for 30 minutes, the 180-degree peel strength (N / 25 mm) was measured at a peel speed of 300 mm / min and evaluated according to the following criteria. [Evaluation criteria] ○:10N / 25mm or more ×: Less than 10N / 25mm
[0153] [Adhesive strength after heating at 180°C before exposure to active energy rays] A 25 mm x 100 mm test piece was prepared from the pressure-sensitive adhesive sheet (S1), the 38 μm polyester release sheet with a light release lining was peeled off, and the piece was pressed and attached to a soda glass plate (manufactured by Nippon Test Panel Co., Ltd.) using a 2 kg rubber roller that was rolled back and forth twice under pressure at 23°C and 50% RH, and then heat-treated for 1 hour at 180°C. The soda glass plate with the heat-treated pressure-sensitive adhesive sheet attached was left to stand for 1 hour in an atmosphere of 23°C and 50% relative humidity, after which the 180-degree peel strength (N / 25 mm) was measured at a peel speed of 300 mm / min and evaluated according to the following criteria. [Evaluation criteria] 〇:10N / 25mm or more △: 3N / 25mm or more, less than 10N / 25mm ×: Less than 3N / 25mm
[0154] [Adhesive strength after heating to 180°C and exposure to active energy rays] A 25mm x 100mm test piece was prepared from the pressure-sensitive adhesive sheet (S1), the 38μm polyester release sheet with a light release property was peeled off, and the test piece was pressed and attached to a soda glass plate (manufactured by Nippon Test Panel Co., Ltd.) in an atmosphere of 23°C and 50%RH by rolling a 2kg rubber roller back and forth twice, and then heat-treated at 180°C for 1 hour. The soda glass plate with the heat-treated pressure-sensitive adhesive sheet attached was then left to stand for 1 hour in an atmosphere of 23°C and 50% relative humidity, after which it was irradiated with ultraviolet light (cumulative irradiation dose 180mJ / cm) from the polyester sheet side using one 80W high-pressure mercury lamp. 2 After leaving the sample for 30 minutes in an atmosphere of 23°C and 50% RH, the 180° peel strength (N / 25 mm) was measured at a peel rate of 300 mm / min. The peeling state was also visually observed and evaluated according to the following criteria. [Evaluation criteria] (Adhesive strength) ◎:1N / 25mm or less ○: 1N / 25mm or more, less than 1.5N / 25mm ×:1.5N / 25mm or more (peeling state) 〇: No glue residue △: There is glue residue ×: Adhesive residue, material destruction, interface peeling on the substrate side
[0155] [Table 3]
[0156] From the results in Table 3 above, the adhesive sheets produced using the active energy ray-curable peel-type adhesive compositions of Examples 1 to 13 had good adhesive strength before irradiation with active energy rays, and also had good adhesive strength after heating at 180°C. When subsequently irradiated with active energy rays, the adhesive strength decreased, and peeling occurred at the interface on the adherend side, leaving little adhesive residue. On the other hand, none of the adhesive sheets produced using the active energy ray-curable peel-type adhesive compositions of Comparative Examples 1 to 7, which did not contain a nitroso compound (C1) as the polymerization inhibitor (C), satisfied all of the adhesive properties before and after irradiation with active energy rays. [Industrial Applicability]
[0157] The pressure-sensitive adhesive composition of the present invention can be suitably used as a pressure-sensitive adhesive sheet for temporary surface protection when processing electronic substrates, semiconductor wafers, processed glass products, metal plates, plastic plates, and the like.
Claims
1. An active energy ray-curable peel-type pressure-sensitive adhesive composition comprising an acrylic resin (A), a urethane (meth)acrylate compound (B), and a polymerization inhibitor (C), The active energy ray-curable peel-type pressure-sensitive adhesive composition, wherein the polymerization inhibitor (C) contains a nitroso compound (C1).
2. The active energy ray-curable peelable pressure-sensitive adhesive composition according to claim 1 , wherein the acrylic resin (A) has a structural unit derived from an alkyl (meth)acrylate (a1).
3. The active energy ray-curable peelable pressure-sensitive adhesive composition according to claim 1 , wherein the acrylic resin (A) has a structural unit derived from a functional group-containing monomer (a2).
4. 2. The active energy ray-curable peelable pressure-sensitive adhesive composition according to claim 1, wherein the acrylic resin (A) has a structural unit derived from a hydroxyl group-containing monomer (a2-1).
5. The active energy ray-curable peelable pressure-sensitive adhesive composition according to claim 4, wherein the content of the structural units derived from the hydroxyl group-containing monomer (a2-1) is 0.1 to 10 mass % of all structural units of the acrylic resin (A).
6. 2. The active energy ray-curable peelable pressure-sensitive adhesive composition according to claim 1, wherein the acrylic resin (A) has a structural unit derived from a carboxy group-containing monomer (a2-2).
7. The active energy ray-curable peelable pressure-sensitive adhesive composition according to claim 6, wherein the content of the structural units derived from the carboxy group-containing monomer (a2-2) is 30 mass % or less of all structural units of the acrylic resin (A).
8. 2. The active energy ray-curable peelable pressure-sensitive adhesive composition according to claim 1, wherein the urethane (meth)acrylate compound (B) has 5 to 20 ethylenically unsaturated groups.
9. The active energy ray-curable peelable pressure-sensitive adhesive composition according to claim 1, wherein the urethane (meth)acrylate compound (B) is a reaction product of a hydroxyl group-containing (meth)acrylate compound having three or more ethylenically unsaturated groups in the molecule and a polyvalent isocyanate compound (b2).
10. 2. The active energy ray-curable peelable pressure-sensitive adhesive composition according to claim 1, wherein the nitroso compound (C1) is ammonium N-nitrosophenylhydroxylamine and / or N-nitrosophenylhydroxylamine aluminum salt.
11. The active energy ray-curable peelable pressure-sensitive adhesive composition according to claim 1, further comprising a crosslinking agent (D).
12. The active energy ray-curable peelable pressure-sensitive adhesive composition according to claim 1, further comprising a photopolymerization initiator (E).
13. A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer crosslinked with the active energy ray-curable peelable pressure-sensitive adhesive composition according to any one of claims 1 to 12.
14. The pressure-sensitive adhesive sheet according to claim 13, wherein the pressure-sensitive adhesive layer is cured and becomes peelable upon irradiation with active energy rays.
Citation Information
Patent Citations
Masking material
JP2019145575A
Pressure sensitive adhesives and pressure sensitive adhesive sheets
JP2020158691A
Workpiece processing sheet
WO2020100491A1